O currículo em uma classe hospitalar: estudo de caso no albergue pavilhão São José da Santa Casa de Misericórdia do Pará - OLANDA, Osterlina Fátima Jucá (2006)
This research purpose to investigate the curricular dynamics implanted by Popular Nucleus of Education Paulo Freire (PNE) of Universidade do Estado do Pará (UEPA), in the hospitalar context, specifically, in the São José Pavillion, by relation which other and which knowledge in the day-byday of the pedagogic relation, by teachers interpretation to curriculum, by alterations of significations and of the knowledges that add, realy, to inclusion and to pedagogic action in hospitalars environments. The theoretical basis that validate this investigation are directioned to aspects of knowledge and construction of curriculum and its particularities, more directly, to practice of curriculum in the day-by-day. By curricular reality of São José Pavillion we can know the curriculum used and interpreted by teachers in this hospitalar class and how this propose is materialized while curricular dynamics. We work with qualitative approach that participate the patient-students that are attended by São José Pavillion of Saint House of Mercy of Pará in the period from 2004 to june 2005. The levy of basis had these supports: the interview with two teachers and the teaching project Coordinator; the analysis of Teaching Project of PNE. The main results point with respect to the necessity of valuation of this educative action front to the health professionals and parents, so that the pupil-patients understand it as way for its pertaining to school cycles; for the courses of Formation of Professors to review the time of the educative action for the principle of the concurrence of events, for the teaching collective allotment, the orientation of resumes in several disciplines and magnifying of the popular culture; for the group form of debate of the contents articulated in classroom, to increase relative the act to study, since this proposal has the pretension to offer to the pupil-patients the access to the school; to search interaction strategies it enters the professionals of health and education; e to investigate this curricular dynamics of more systematic and constant form to develop the educative process in hospital environment.